Levan-based hydrogels for controlled release of Amphotericin B for dermal local antifungal therapy of Candidiasis - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP (ELSEVIER, 2020)
Hydrogels from Halomonas levan polysaccharide were prepared at different crosslinking densities. Swelling results demonstrated pH dependent rather than temperature dependent swelling of the hydrogel and the highest swelling value was achieved at basic conditions with a swelling ratio of 9.1 +/- 0.1 which is the highest reported for levan based hydrogels. SEM images show a porous network architecture, which indicates a large surface area of the hydrogels. Rheological analyses showed the viscoelastic behavior of the hydrogels. Biocompatibility of the hydrogels was confirmed by cell culture experiments. For drug release experiments Amphotericin B (AmB) was used. 51% of the loaded AmB was released into the PBS buffer and the released AmB had a significant antifungal activity against Candida albicans.
Keywords: Halomonas Levan; Hydrogel; Amphotericin B; Controlled drug release; Antifungal activity; Wound healing; HALOMONAS-SMYRNENSIS; SILVER NANOPARTICLES; COMPLEXATION; BINDING; SYSTEM; FILMS; GEL